Effects of a peer-mediated performance improvement intervention on recording of child well-body checks by educational care-providers. (March 2021) - Hartz, Renee M; Butler, Brittany L; Natale, Kerianne R; Williams, Stacey; Luiselli, James K
We report the effects of peer-mediated training as a performance improvement intervention on recording of well-body checks by classroom instructors at a specialized school for children and youth. The instructors were trained as peer mediators and then assumed performance monitoring responsibilities in the classroom. Compared to baseline phases in a withdrawal design, peer-mediation increased recording of well-body checks to near-100% among the instructors. Results of the study document positive training effects on a critical health and wellness objective, support and expand the limited research base concerning the effects of peer-mediated training, suggest further application of such training in human services settings.